2015
DOI: 10.1016/j.chom.2015.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota-Dependent Priming of Antiviral Intestinal Immunity in Drosophila

Abstract: Summary Enteric pathogens must overcome intestinal defenses to establish infection. In Drosophila, the ERK signaling pathway inhibits enteric virus infection. The intestinal microflora also impacts immunity but its role in enteric viral infection is unknown. Here we show that two signals are required to activate antiviral ERK signaling in the intestinal epithelium. One signal depends on recognition of peptidoglycan from the microbiota, particularly from the commensal Acetobacter pomorum, which primes the NF-kB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
161
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 144 publications
(168 citation statements)
references
References 78 publications
(112 reference statements)
5
161
2
Order By: Relevance
“…When these studies were extended to the gut epithelium, it was observed that priming by the microbiota was necessary for robust induction of Pvf2 in the intestinal epithelium following viral infection. The mechanism of priming of the microbiota however requires components of the Imd pathway (Imd, Tak1) and the NF-κB factor Relish, but not the Toll pathway [110], which seems in contrast to the previously mentioned study [94]. Both studies also found different effects of antibiotics on the antiviral defense mechanism (no effect: [94]; proviral effect: [110]).…”
Section: Involvement Of Innate Antimicrobial Immune Pathways (Toll Anmentioning
confidence: 75%
See 4 more Smart Citations
“…When these studies were extended to the gut epithelium, it was observed that priming by the microbiota was necessary for robust induction of Pvf2 in the intestinal epithelium following viral infection. The mechanism of priming of the microbiota however requires components of the Imd pathway (Imd, Tak1) and the NF-κB factor Relish, but not the Toll pathway [110], which seems in contrast to the previously mentioned study [94]. Both studies also found different effects of antibiotics on the antiviral defense mechanism (no effect: [94]; proviral effect: [110]).…”
Section: Involvement Of Innate Antimicrobial Immune Pathways (Toll Anmentioning
confidence: 75%
“…The necessity for tight control of immune pathways to prevent pathological damage from excessive activation has also been reported for the JAK/STAT pathway and is related to the concept of virus "tolerance" rather than "resistance" ( [79,151,152]; see also section 3.4). As already mentioned in section 3.2.4, RNAi screens identified a signaling circuit involving PVR, its ligand Pvf2 and ERK signaling, that controls DCV and arbovirus (including SINV) infections [110]. When these studies were extended to the gut epithelium, it was observed that priming by the microbiota was necessary for robust induction of Pvf2 in the intestinal epithelium following viral infection.…”
Section: Involvement Of Innate Antimicrobial Immune Pathways (Toll Anmentioning
confidence: 86%
See 3 more Smart Citations